2018
DOI: 10.1126/sciimmunol.aal2736
|View full text |Cite
|
Sign up to set email alerts
|

Production of BMP4 by endothelial cells is crucial for endogenous thymic regeneration

Abstract: The thymus is extremely sensitive to damage but also has a remarkable ability to repair itself. However, the mechanisms underlying this endogenous regeneration remain poorly understood and this capacity diminishes considerably with age. Here we show that thymic endothelial cells (ECs) comprise a critical pathway of regeneration, via their production of BMP4. ECs increased their production of BMP4 after thymic damage, and abrogating BMP4 signalling or production by either pharmacologic or genetic inhibition imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
160
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(164 citation statements)
references
References 70 publications
(120 reference statements)
3
160
1
Order By: Relevance
“…In conclusion, our study further extends the pervasive role of Foxn1 in thymus biology, as it was shown to be involved in all models of thymic growth, regeneration, and involution to this day (14,15,34,53,55,56). Also, unlike what is observed following irradiation-induced involution (15), no evidence of BMPR signaling or of damage to the epithelial population was detected in postpartum thymic regeneration. These data imply that the mechanisms involved in triggering thymic regeneration differ depending on the context leading to thymic involution.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In conclusion, our study further extends the pervasive role of Foxn1 in thymus biology, as it was shown to be involved in all models of thymic growth, regeneration, and involution to this day (14,15,34,53,55,56). Also, unlike what is observed following irradiation-induced involution (15), no evidence of BMPR signaling or of damage to the epithelial population was detected in postpartum thymic regeneration. These data imply that the mechanisms involved in triggering thymic regeneration differ depending on the context leading to thymic involution.…”
Section: Discussionsupporting
confidence: 73%
“…A recent study showed that secretion of BMP4 by thymic endothelial cells promotes thymic regeneration following acute involution induced by sub-lethal total body irradiation (15). Increased BMP4 signaling was observed in thymic stromal cells 4-7 days following irradiation, and was accompanied by an upregulation of Foxn1 and its target genes in TECs.…”
Section: Expression Of Foxn1 Is Modulated During Postpartum Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Its receptor, Bmpr2, is primarily expressed on cTEC lo and mTEC lo progenitors (42), and was proposed to have a role in maintaining progenitor populations at the expense of differentiation (10). However, Bmp4 induced self-renewal of progenitors may also have a role in thymus regeneration following damage, as demonstrated following irradiation (43).…”
Section: Discussionmentioning
confidence: 99%